Proceedings of Second International Conference in Mechanical and Energy Technology ICMET 2021, India - Yadav, Sanjay; Haleem, Abid; Arora, P. K.; Kumar, Harish (Smart innovation, systems and technologies, 2023)
This book presents selected peer-reviewed papers from the International Conference on Mechanical and Energy Technologies, which was held on October 28–29, 2021, at Galgotias College of Engineering and Technology, Greater Noida, India. The book reports on the latest developments in the field of mechanical and energy technology in contributions prepared by experts from academia and industry. The broad range of topics covered includes aerodynamics and fluid mechanics, artificial intelligence, nonmaterial and nonmanufacturing technologies, rapid manufacturing technologies and prototyping, remanufacturing, renewable energies technologies, metrology and computer-aided inspection, etc. Accordingly, the book offers a valuable resource for researchers in various fields, especially mechanical and industrial engineering, and energy technologies.